2020
DOI: 10.1002/marc.202000359
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Damage Detection in an Elastomer Nanocomposite with a Coumarin Dimer Mechanophore

Abstract: resistance that result from dispersing stiffer particulates or fibers into the softer polymer matrix. [2,3] In high performance polymer composites, mechanical performance is often determined by how stress transfer from the matrix to the filler either prevents or facilitates the formation of voids, depending on the mechanism of toughening. [4,5] Stress overload can lead to the scission of covalent bonds or chain slippage and induce irreversible structural changes at the molecular, mesoscopic, and macroscopic le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 51 publications
(58 reference statements)
1
28
0
Order By: Relevance
“…[ 25 ] Sources of relaxation dynamics include dangling chain ends and the interactions of network chains with nano‐silica filler, and mechanophores might be useful in probing the molecular origins of high strain rate behavior. In particular, the placement of mechanophores within the elastomers [ 26 ] (e.g., cross‐links versus mid‐chain versus at the interface of fillers) can be controlled through synthesis, which might be useful in elucidating the molecular details of the various processes. We suggest that this understanding might be especially relevant to the early stages of material damage, because the tension required for mechanophore activation (100s of pN) corresponds to polymer chains (or partial subchains) that are fully stretched beyond the conformational entropy dominated regime, [ 18 ] to a point where chain scission is increasingly likely.…”
Section: Figurementioning
confidence: 99%
“…[ 25 ] Sources of relaxation dynamics include dangling chain ends and the interactions of network chains with nano‐silica filler, and mechanophores might be useful in probing the molecular origins of high strain rate behavior. In particular, the placement of mechanophores within the elastomers [ 26 ] (e.g., cross‐links versus mid‐chain versus at the interface of fillers) can be controlled through synthesis, which might be useful in elucidating the molecular details of the various processes. We suggest that this understanding might be especially relevant to the early stages of material damage, because the tension required for mechanophore activation (100s of pN) corresponds to polymer chains (or partial subchains) that are fully stretched beyond the conformational entropy dominated regime, [ 18 ] to a point where chain scission is increasingly likely.…”
Section: Figurementioning
confidence: 99%
“…What is already known is that the stress transfer within the complex composites determines the overall mechanical properties, a build-in sensitive stress probe thus would be helpful for understanding their complex mechanical behaviors. [26][27][28] Herein, with the dispersion of different surface-modified Janus nanofillers (sheets or hollow spheres) into the 1,2-dioxetane containing Semi-IPNs, a new kind of mechanochemiluminescent Semi-IPNs nanocomposites with enhanced mechanical properties and stress-reporting capability were developed. Comprehensive characterizations based on fourier transform infrared spectroscopy (FT-IR), differential scanning calorimetry (DSC), scanning electronic microscope (SEM), and tensile tests demonstrated that the hierarchically crosslinked structures, including H-bond interactions mediated by Janus nanoparticles and chemical crosslinking within Semi-IPNs, jointly contributed to excellent mechanical properties of the composites.…”
Section: Doi: 101002/marc202000442mentioning
confidence: 99%
“…What is already known is that the stress transfer within the complex composites determines the overall mechanical properties, a build‐in sensitive stress probe thus would be helpful for understanding their complex mechanical behaviors. [ 26–28 ]…”
Section: Figurementioning
confidence: 99%
“…[8] These examples illustrate that mechanically induced color changes in polymers can be achieved by very different mechanisms that include physical at the molecular scale in such polymers. [13] Hideyuki Otsuka's team demonstrate that multicolor mechanochromism in mixtures of two mechanochromic polystyrene samples containing different mechanochromophores allows one to detect the duration mechanical stimulation. [14] In their communication on semi-interpenetrating elastomer network nanocomposites containing Janus nanoparticles and a mechanoluminescent motif, Yulan Chen and co-workers further raise the bar with respect to complexity.…”
mentioning
confidence: 99%
“…Stephen L. Craig's group shows that mechanophores based on coumarin dimers exhibit a strength that is comparable to that of sulfur‐sulfur bonds that represent the weakest bonds in vulcanized rubbers and allowed them to investigate how macroscopic mechanical stress is transferred at the molecular scale in such polymers. [ 13 ] Hideyuki Otsuka's team demonstrate that multicolor mechanochromism in mixtures of two mechanochromic polystyrene samples containing different mechanochromophores allows one to detect the duration mechanical stimulation. [ 14 ] In their communication on semi‐interpenetrating elastomer network nanocomposites containing Janus nanoparticles and a mechanoluminescent motif, Yulan Chen and co‐workers further raise the bar with respect to complexity.…”
mentioning
confidence: 99%